Métaphysique et éthique de la liberté - Moulin, Isabelle (Revue des sciences religieuses, 2023)
After putting Olivier Boulnois' own method into perspective within the field of philosophical methods, the article develops the book's key concepts, especially the question of freedom in its relation to free will and the will, and in its opposition to determinism. It then looks in more detail at four key points to emerge from the book : the dynamic conception of freedom, the unity of human faculties, the theoretical construction of choice, and the katholou-protological dimension of freedom.